The Shifting Dynamics of Work-Life Balance for Accounting Lecturers: Insights from Remote and Hybrid Teaching Models - Amri, Abrar; Soufyan, Dara; Mahdani, Rimal (LP2M IAIN Palopo, 2025)
This study seeks to address to finding a balance between work, family, and personal well-being is not only crucial for the professional success of faculty members but also for their mental and physical health by examining how the shift to remote and hybrid work models impacts the work-life balance of accounting lecturers. This study used a qualitative online survey to gather a wide range of perspectives and experiences from accounting lecturers that employed a ‘Big Q’ approach, using open-ended questions to encourage detailed and reflective responses. To identify common themes and patterns within the data, thematic analysis was used. The findings suggest that remote work has profound implications for both the personal and professional lives of accounting lecturers, affecting their work-life balance, productivity, and overall work dynamics. While remote work offers considerable benefits, such as increased flexibility and improved work-life balance, it also presents challenges that must be carefully managed to maximize its positive impact. The findings of this study complement accounting literature that has mainly focused on the traditional work paradigm, requiring in-person presence. The authors identify potential challenges emanating from accounting lecturer work and propose solutions for university to improve work-life balance in a work setting. While this study provides valuable insights, future research should focus on longitudinal studies to better understand the sustained effects of remote work on academic performance, job satisfaction, and career longevity.